2019
DOI: 10.1101/mcs.a004218
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of heterozygous germline RECQL4 loss-of-function variants in pediatric osteosarcoma

Abstract: Patients harboring germline pathogenic biallelic variants in genes involved in the recognition and repair of DNA damage are known to have a substantially increased cancer risk. Emerging evidence suggests that individuals harboring heterozygous variants in these same genes may also be at heightened, albeit lesser, risk for cancer. Herein, we sought to determine whether heterozygous variants in RECQL4, the gene encoding an essential DNA helicase that is defective in children with the autosomal recessive cancer-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…ABCB11 mutations also confer increased risk of developing HCC (72-77), but only in a recessive mode of inheritance, such as the FAH gene. Interestingly, emerging evidences suggest that individuals harboring germline variants in heterozygosity in autosomal recessive cancer predisposition genes may also be at increased cancer risk (78)(79)(80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABCB11 mutations also confer increased risk of developing HCC (72-77), but only in a recessive mode of inheritance, such as the FAH gene. Interestingly, emerging evidences suggest that individuals harboring germline variants in heterozygosity in autosomal recessive cancer predisposition genes may also be at increased cancer risk (78)(79)(80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that pediatric/embryonal tumors and congenital anomalies share common etiologic factors underlying their development, and this is a relevant and ongoing discussion in the literature. Particularly, there is a relevant association between craniosynostosis and renal/genital anomalies with HB development (76)(77)(78)(79)(80), suggesting a yet unknown common molecular mechanism. In our cohort, five patients exhibited congenital renal anomalies, and the syndromic patient had craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing methods used were highly variable across the studies ( Table 3 and Supplementary Data 1:T1). Of the studies in this review, 10 indicated that they used one or more forms of NGS sequencing (whole-exome, whole-genome, RNA-seq) and thus were able to sample CH variants broadly (Valentine et al, 2014;Spinella et al, 2015;Zhang et al, 2015Zhang et al, , 2018Diets et al, 2018;Diness et al, 2018;Gröbner et al, 2018;Waszak et al, 2018;Maciaszek et al, 2019;Schieffer et al, 2019). Thirteen studies indicated that they used non-NGS methods (Sanger, Direct sequencing, SNP-array, Multiplex ligation-dependent probe amplification) and were therefore limited in the number of genes and CH variants analyzed (Quesnel et al, 1999;De Rosa et al, 2000;Østergaard et al, 2005;Okkels et al, 2006;Scott et al, 2007;Herkert et al, 2011;Leenen et al, 2011;Chmara et al, 2013;Bakry et al, 2014;Piane et al, 2016;Svojgr et al, 2016;Moriyama et al, 2017;Sharapova et al, 2018).…”
Section: Methodsologies Used To Identify Ch Variants and Assess Pathogmentioning
confidence: 99%
“…Across all studies, cancer types with more than 10 samples included AML, ALL, high-grade glioma, medulloblastoma (Valentine et al, 2014;Zhang et al, 2015;Diets et al, 2018;Gröbner et al, 2018). Thirteen studies evaluated a single patient (Quesnel et al, 1999;De Rosa et al, 2000;Okkels et al, 2006;Scott et al, 2007;Peters et al, 2009;Majumdar et al, 2010;Chmara et al, 2013;Piane et al, 2016;Diness et al, 2018;Salih et al, 2018;Sharapova et al, 2018;Maciaszek et al, 2019;Schieffer et al, 2019).…”
Section: Genementioning
confidence: 99%
See 1 more Smart Citation